Monetary policy governance: Bank of Canada practices to support policy effectiveness - Brigitte Desroches; Sharon Kozicki; Laure Simon (Bank of Canada, 2024)
Monetary policy governance - how monetary policy objectives are determined, how decisions are made and who makes them - determines the quality and effectiveness of monetary policy decisions. In this paper, we examine some desirable and some adverse outcomes associated with different governance structures. We discuss the roles of legislation, institutional features, and processes and practices in establishing various aspects of governance. We highlight the importance of the domestic context in determining what governance structure works best for a given central bank. Finally, we provide an update on monetary policy governance at the Bank of Canada and how it has evolved over time
Keywords: E02; E5; E58; 330; Credibility; Monetary policy communications; Monetary policy framework